2011
DOI: 10.1158/1078-0432.ccr-11-0043
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Breast Cancer Estrogen Disposition: The Basis for Endocrine Manipulation

Abstract: Although normal breast tissue and breast cancer estrogens are known to be elevated compared with plasma estrogen levels, the mechanism behind this phenomenon has been an issue of debate for 2 decades. If local estrogen aromatization were to be confirmed as the main estrogen source in breast cancer tissue, tissue-specific inhibition of estrogen production, avoiding systemic side effects, would become a potentially attractive option for breast cancer treatment and prevention. Based on recent results from our gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 87 publications
0
29
1
2
Order By: Relevance
“…CYP19 is expressed both in normal breast and breast cancer tissue [10]. However, due to a rapid plasma to tissue transfer rate, the key factor regulating normal breast as well as breast cancer tissue estrogen levels is the plasma hormone concentration [29][30]. Thus, any factor influencing estrogen synthesis in any body compartment subsequently leading to alterations in plasma estrogen levels should influence normal breast and breast cancer tissue estrogen levels as well.…”
Section: Discussionmentioning
confidence: 99%
“…CYP19 is expressed both in normal breast and breast cancer tissue [10]. However, due to a rapid plasma to tissue transfer rate, the key factor regulating normal breast as well as breast cancer tissue estrogen levels is the plasma hormone concentration [29][30]. Thus, any factor influencing estrogen synthesis in any body compartment subsequently leading to alterations in plasma estrogen levels should influence normal breast and breast cancer tissue estrogen levels as well.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence points to this as the source of oestrogen driving breast cancer development in these women. Correlations of plasma oestradiol levels with the expression of oestrogen-regulated genes in breast cancer tissue support this concept (Dunbier et al 2008, Lonning et al 2011. A number of reports show a correlation between circulating levels of oestrogens and breast cancer risk (see below), but this does not mean that circulating levels are necessarily the drivers of breast cancer; rather they reflect the ongoing synthesis of oestrogens within the adipose tissue, some of which gets into the circulation.…”
Section: Source Of Oestrogensmentioning
confidence: 98%
“…In the present study, we found that E 2 could dose-dependently promote the migration of MCF-7 breast cancer cells via up-regulation of MRTF-A and its target genes, MYL9 and CYR61. In addition, these effects were dramatically increased when the concentration of E 2 was higher than 10 29 M. It was reported that the plasma concentration of serum estradiol typically fluctuates in a wide range of 1.7-7.5 Â 10 210 M in the normal menstrual cycle of adult female, and it always decreases to about 1.5-2.5 Â 10 211 M in postmenopausal women [16,17]. Therefore, our results suggested that the MRTF-A signal pathway could be markedly activated when the breast cancer cells were exposed to estrogen at higher physiological levels, and this event might contribute to the excessive estrogen-stimulated breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%